Functional analysis of a latex-specific promoter (hevein) of Hevea for enhanced recombinant protein production in Hevea brasiliensis - Pappusamy, Arokiaraj / PA; Shuib, Siti Shuhada; Enamalai, Sunderasan (2011)
Any protein, either naturally occurring or designed synthetically, could be produced safely, inexpensively and in large quantities using the power of the rubber trees for the production of recombinant proteins on a plantation scale with sunlight and water. In the past, the Rubber Research Institute of Malaysia has generated transgenic Hevea that expressed recombinant human serum albumin, scFv antibody in latex serum. However, the production is still below the 1.0 % level for commercial feasibility. This study evaluates the promoter activity of hevein gene, which encodes the most abundant soluble protein in Hevea latex. Genetic constructs were prepared with the test hevein promoter fragments Hev P1 (0.35kb), Hev P2 (0.45kb) and Hev P3 (0.73kb) that were inserted 5’ to the reporter gene uidA in pGPTV-KAN expression vector. The expression vectors containing the hevein promoter fused to uidA in Agrobacterium tumefaciens GV2260 were then used to infect Hevea anther callus. Putative transgenic rubber plantlets generated via somatic embryogenesis tested for gene insertion, gave signals for single and mutiple copies for uidA gene and this was similarly reflected in the positive control (plants with 35S CaMV promoter) by Southern analysis. The recombinat protein levels for β-glucuronidase (GUS) in the latex of Hevea transformants and controls was quantified using ELISA technique. The levels of GUS in latex serum from positive controls (B6 plants) ranged from 0.063 to 0.079 µg/ml of latex serum. The levels of GUS protein (µg/ml of latex serum) in Hevea transformants P1 ranged from 0.0052 to 1.55; P2 ranged from 0.005 to 0.0012; P3 ranged from 0.0017 to 0.0027. The highest expressing transgenic plants was derived from B6 using the 35S CaMV promoter for uidA gene and P1 containing the smallest fragment of the hevein promoter for uidA gene. This study paves the way to sucessfully produce recombinant proteins of commercial value in transgenic rubber trees.